A Systematic Review of Replicative Self-Determination Intervention Studies. (May 2020) - Luckner, John L.; Banerjee, Rashida; Movahedazarhouligh, Sara; Millen, Kaitlyn
Current federal legislation emphasizes the use of programs, interventions, strategies, and activities that have been demonstrated through research to be effective. One way to increase the quantity and quality of research that guides practice is to conduct replication research. The purpose of this study was to undertake a systematic review of the replication research focused on self-determination conducted between 2007 and 2017. Using methods used by Cook and colleagues, we identified 80 intervention studies on topics related to self-determination, of which 31 were coded as replications. Intervention study trends, rate of replication studies, percentage of agreements between findings of original and replication studies, amount of author overlap, and types of research designs used are reported along with recommendations for future research.